Impact of Instructions on the Developmental Status of Premature Infants on the Clinical Practice of Neonatal Intensive Care Unit (NICU) Nurses - Fatemeh Bakhshi; Sedigheh Montaser; Mitra Edraki; Mostajab Razavi Nejad; Sezaneh Haghpanah (Mashhad University of Medical Sciences, 2018)
Background: Stabilization of the conditions of infants is essential to the neurodevelopmental interventions in neonatal intensive care units (NICUs). Premature infants are born before the third trimester of pregnancy is completed, which disrupts the evolutionary process associated with brain development in neonates. Given the importance of the position of preterm infants and limited findings on nursing education in NICUs, the present study aimed to conduct a training intervention to improve the performance of nurses to properly implement the evolutionary positions of premature infants in the NICU. We also investigated the impact of instructions on the evolutionary status of preterm infants on the clinical practices in the NICUs of the hospitals affiliated to Iran University of Medical Sciences.Methods: This quasi-experimental study was conducted on 85 NICU nurses selected via convenience sampling. Performance of the nurses in implementing the evolutionary supportive status on the preterm infants admitted to the NICU was assessed and compared using a neonatal assessment tool before, one week, and two months after the intervention.Results: Analysis of the demographic data indicated that the majority of the NICU nurses had a master's degree (98.8%), most of whom were aged more than 30 years (48.2%). Nurses constituted the majority of the participants (97.6%), who had the highest work experience (5-10 years) (42.4%). A significant difference was observed in the performance scores of nurses in the evolutionary support status of premature infants before, one week, and two months after the training (P>0.001).Conclusion: According to the results, training on the emergency support status of premature infants had a positive effect on the nursing performance in NICUs.